COMT val158met is not associated with Aβ-amyloid and APOE ε4 related cognitive decline in cognitively normal older adults. (June 2019) - Porter, Tenielle; Burnham, Samantha C.; Milicic, Lidija; Savage, Greg; Maruff, Paul; Sohrabi, Hamid R.; Peretti, Madeline; Lim, Yen Ying; Weinborn, Michael; Ames, David; Masters, Colin L.; Martins, Ralph N.; et al.
Highlights: Effect of COMT Val158Met on cognitive decline in preclinical AD investigated. Impact on Aβ-amyloid and APOE ε4 mediated decline assessed. COMT does not influence Aβ-amyloid or APOE ε4 driven cognitive decline. Abstract: The non-synonymous single nucleotide polymorphism (SNP), Val158Met within the Catechol- O -methyltransferase ( COMT ) gene has been associated with altered levels of cognition and memory performance in cognitively normal adults. This study aimed to investigate the independent and interactional effects of COMT Val158Met on cognitive performance. In particular, it was hypothesised that COMT Val158Met would modify the effect of neocortical Aβ-amyloid (Aβ) accumulation and carriage of the apolipoprotein E ( APOE) ε4 allele on cognition in preclinical Alzheimer's disease (AD). In 598 cognitively normal older adults with known neocortical Aβ levels, linear mixed modelling revealed no significant independent or interactional associations between COMT Val158Met and cognitive decline. These findings do not support previous associations between COMT Val158Met and cognitive performance and suggest this variant does not influence Aβ-amyloid or APOE ε4 driven cognitive decline in a well characterised cohort of cognitively normal older adults.